2002
DOI: 10.1161/01.str.0000038424.70926.5e
|View full text |Cite
|
Sign up to set email alerts
|

Visual Rating Scales for Age-Related White Matter Changes (Leukoaraiosis)

Abstract: Background and Purpose-It has been hypothesized that the use of different visual rating scales partly explains the discordant results of studies investigating risk factors and clinical correlates of age-related cerebral white matter changes (leukoaraiosis). We aimed to compare 6 widely used rating scales for leukoaraiosis and to calculate conversion coefficients of the score of 1 scale in the score of a second scale. Methods-Two trained raters evaluated 80 pairs of CT and MRI scans using 2 CT and 4 MRI rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…Again, this could be explained by the low age and high MMSE of our patients. 38 The dominant finding of our study is that CDF is almost constant within the first month after stroke and related to working memory deficit with some executive and memory dysfunction, whereas instrumental functions were relatively spared. One of the strengths of this study derives from the use of MRI in all patients, which allow more reliable diagnosis of recent strokes, silent strokes, and leukoaraiosis.…”
Section: Discussionmentioning
confidence: 56%
“…Again, this could be explained by the low age and high MMSE of our patients. 38 The dominant finding of our study is that CDF is almost constant within the first month after stroke and related to working memory deficit with some executive and memory dysfunction, whereas instrumental functions were relatively spared. One of the strengths of this study derives from the use of MRI in all patients, which allow more reliable diagnosis of recent strokes, silent strokes, and leukoaraiosis.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it is essential to extend our findings using automated methods for WMH evaluation in more representative samples of HF subjects. Nevertheless, it is interesting to mention that recent studies of WMH in elderly subjects have reported similar findings either with automated assessment methods or the visual method of Scheltens (20).…”
Section: Control (N = 14)mentioning
confidence: 71%
“…40 Several visual scales were proposed to quantify the extent of LA 40 with variable score spans and interobserver reproducibility. Overall, no or weak correlation with quantitative measurements of cognitive deficit was observed in cross-sectional studies evaluating a small sample of patients, 5-7,13-15 whereas on greater sample sizes, typically of hundreds of patients, correlation among the extent of LA, global cognitive impairment, executive dysfunctions, and slowing of mental processing was observed.…”
Section: Discussionmentioning
confidence: 99%